A Comparison of Drug Shortages in the Hospital Setting in the United States and Saudi Arabia: An Exploratory Analysis. Issue 5 (May 2016) - Alsheikh, Mona; Seoane-Vazquez, Enrique; Rittenhouse, Brian; Fox, Erin R.; Fanikos, John
Background: Drug shortages are a problem that has been growing in recent years. This problem has an impact on patient outcomes and public health. Most countries have been affected by a diversity of drug supply chain problems. Objective: To assess explanations for differences in drug shortages reported in the hospital setting in Saudi Arabia (SA) and the United States (US). Methods: Data were collected in May-June 2014 from Brigham and Women's Hospital (BWH) and from 2 Saudi hospitals: King Abdulaziz University Hospital (KAUH) and King Faisal Specialist Hospital and Research Centre (KFSHRC). Drugs were classified using the World Health Organization (WHO) Anatomical Therapeutic Chemical (ATC) classification system. The drug shortages among the hospitals were compared using descriptive statistics and a chi-square test. Results: The percentage of the total number of active ingredients reported in shortage was higher in the US hospital setting (15.1%) than in the Saudi hospitals (10.3%) ( p < .0001). KAUH reported the highest number of shortages ( n = 133), followed by BWH ( n = 42) and KFSHRC ( n = 27). A significantly higher percentage of shortages involved injectable drugs in the US hospital setting (78.1%) than the Saudi hospitals (34.43%) ( p ≤ .0001). Nervous system (17%) and alimentary tract and metabolism agents (15.7%) were the therapeutic areas with the higher number of reported shortages in the US and SA hospital settings, respectively. Conclusions: The number and characteristics of shortages varied by country and hospital. Several factors, including differences in hospital characteristics, number and type of drugs available, and procurement systems, may explain differences in reported shortages.